The Historical Fertility Transition: A Guide for Economists - Guinnane, Timothy W (Journal of Economic Literature, 2011)
The historical fertility transition is the process by which much of Europe and North America went from high to low fertility in the nineteenth and early twentieth centuries. This transformation is central to recent accounts of long-run economic growth. Prior to the transition, women bore as many as eight children each, and the elasticity of fertility with respect to incomes was positive. Today, many women have no children at all, and the elasticity of fertility with respect to incomes is zero or even negative. This paper discusses the large literature on the historical fertility transition, focusing on what we do and do not know about the process. I stress some possible misunderstandings of the demographic literature, and discuss an agenda for future work. (JEL I12, J13, N30)